Pengaruh Suhu Awal Media Pendingin Terhadap Kekerasan dan Kekuatan Impact pada Baja Karbon Medium yang Diperlakukan Quenching - Rendisetyo Rendisetyo (Universitas Negeri Malang, 2020)
Abstract: The porpose of this study was find out the effect of intial temperatur colling medium on harness and toughness of medium steel carbon with quenching prosess. The steel will be used is S50C and the cooling medium with value viscosity of 20-40. The research methods used is kuantitatif with pre-eksperiment design and one-group spesimen control and spesimen eksperimen category. The variation initial temperature colling medium used is 300C, 350C, 450C dan 550C. The results of this study indicate there is an increase in the value of hardness in line with an increase in oil temperature. At a temperature of 300C has a hardness value of 204.39 HVN and a toughness of 0.0618 Joules / mm, at a temperature of 350C a hardness value of 255.14 HVN and a toughness of 0.0478 joules / mm, 450C has a hardness value of 271.03 HVN and a toughness of 0.048 Joules / mm. And at 550C the value of hardness is 234.11 HVN and the toughness is 0.0525 Joules / mm. Keywords: temperature of oil, hardness, toughness, Steel S50C, Quenching.